Survey of university students - Evaluation of teaching : an integrated approach to promoting a quality culture - EL YADARI , ABDELBASSET (Revue Internationale du Chercheur, 2024)
The article points out that the assessment of teachers by students is of crucial importance and fully aligns with the process of continuous improvement in education. It aims to obtain valuable feedback from students to identify strengths to be emphasized and weaknesses to be addressed in our teaching. This approach allows us to make necessary corrections, evolve our pedagogical practices, and ensure a quality learning experience. By paying particular attention to the engagement of learners in expressing their satisfaction or dissatisfaction with the content and pedagogical methods offered to them, we enhance the credibility and validity of any pedagogical reform. Students thus become active participants in their own education, and their voice becomes an essential component for evaluating the effectiveness of our teachers and the education system as a whole. The survey carried out among students at Hassan II University reveals general dissatisfaction with what the university has to offer, the equipment available, the teaching methods adopted, the quality of training and the performance of human resources. These results underline the importance of systematically incorporating student feedback into improvement processes.